MANAGEMENT OF INTELLECTUAL PROPERTY IN AI-GENERATED ARTWORKS - Sharma, Tripti; J Jabez; Agarwal, Varsha; Sachdeva, Ankit; Velvizhi K; Kaur, Ashmeet (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With the fast development of artificial intelligence, the creative industries were changing, as machines can produce highly developed works of art that question the conventional concept of creativity, authorship, and property rights. With the rising popularity of AI-generated art, the intellectual property (IP) law and policy concerning AI-generated art have become a pressing legal and policy concern. This paper explores the intellectual basis of AI-created pieces of art, emphasizing the role of human elements and machine-directed algorithms leading to the overall artistic work. It then makes an assessment of the existing intellectual property rights systems such as copyright, patents, trademarks and moral rights to see how they apply to AI-assisted and fully autonomous works. The legal issues in the center are examined, and specific focus is made on the questions of authorship attribution, allocating ownership and copyright deserving, and liability of developers, users and AI systems in cases of infringement. Comparative analysis of approaches in the world has shown that there is a great variance that exists among the jurisdictions. The United States tends to use a model of authorship that is more human-focused, restricting the copyright rights of the work that does not imply significant human contribution. The European Union gives the priority to human intellectual creative but is seeking alternative regulation solutions. Asian jurisdictions including Japan, China and India are actively evolving guidelines to find a balance between innovation and legal certainty with each having its own policy orientation. International organizations specifically WIPO are trying to make global standards harmonize despite different national interpretations.